Weedy rice (Oryza sativa) I. Grain characteristics and growth response to competition of weedy rice variants from five Asian countries - Chauhan, Bhagirath S.; Johnson, David E. (Cambridge University Press, 2010)
Weedy rice is a serious weed of cultivated rice in most of the rice-growing areas of the tropics and yet, despite its importance as a weed, limited information is available on its biology in Asia. A study was conducted to determine the seed characteristics and growth response to competition of weedy rice variants from five Asian countries (India [IWR], Malaysia [MWR], Philippines [PWR], Thailand [TWR], and Vietnam [VWR]) when grown alone or with either 4 or 12 cultivated rice (‘IR72’) plants. Seed characteristics including weight, length, width, and presence and length of awn differed between weedy rice variants. PWR had the heaviest seed (25 mg seed−1). Growth of weedy rice plants differed among variants and, generally, VWR grew the fastest. IR72 interference greatly reduced tiller and leaf numbers, leaf area, and shoot biomass of all weedy rice variants. At 8 wk after sowing, for example, shoot biomass of weedy rice variants in competition with 12 IR72 plants was 13 to 30% of that where plants were grown alone. TWR plants were shorter than those of other variants at all levels of crop interference. These results show that there are considerable differences among Asian weedy rice variants and yet, competition from the rice crop greatly suppresses weedy rice growth. This suggests that measures to ensure a competitive crop should be an important component of control strategies.